Accommodating the Third Space in a Fourth Society: BDAFRICA, a groundbreaking source for the analysis of African Literature Reception in Spain - Fernandez-Ruiz, Maria (My University, 2018)
Inherent features of African postcolonial literature have hampered reception quan- tification, which is even more often neglected in countries with limited experience of African decolonization processes. This has been exemplified through the Spanish case, where there was no quantitative data available to report on current recep- tion trends. Hence, by exploiting the BDAFRICA database, a relevant specialized bibliographical research tool, we have provided an unparalleled study that covers 42 years of African literature reception in Spain (1972–2014). The methods described in this paper are descriptive. Quantitative information that is subject to a descriptive analysis has been selected from BDAFRICA. The results provide clear evidence of the sustained increase in the production of African fiction books and offer academia unparalleled data, thereby opening the door to manifold research lines.
PUBLISHED
Keywords: bibliographical database; BDAFRICA; descriptive statistics; book market reception; African postcolonial literature; postcolonial translation